Effect of feeding bypass protein with and without biopromotors on milk production, and certain rumen and blood metabolites in lactating Murrah buffaloes - Akbar, M A; Kuldip, Kuldip; Kumari, R; Singh, N (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to assess the effect of feeding bypass protein with or without biopromotors on milk production and certain rumen and blood metabolites in 25 lactating Murrah buffaloes. The animals were randomly divided into 5 groups of 5 each on the basis of nearness in body weight, lactation length and daily milk yield following a completely randomized design. The experiment was carried out far a period of 90 days. The animals in control group (Tâ‚) were fed conventional concentrate mixture as per their requirement. In group Tâ‚‚ , 10 g biopromotors (consisting of live yeast culture) were fed with the concentrate mixture of Tâ‚ In group Tâ‚ƒ , animals were fed 50% conventional concentrate mixture to that of Tâ‚ and the remaining protein requirement was met by supplementing the ration with the whole concentrate treated with formaldehyde. In group Tâ‚„, animals were fed as in Tâ‚ƒ along with 10 g biopromotors. In group Tâ‚…, animals were fed 200 g commercially available mixture of bypass protein and biopromotors (containing Saccharomyces cerevisae 1.4 x 10â¹ m cfu along with growth medium 10g , niacin 1 g, selenium 2.5 g and full fat soya protected bypass protein 188.75 g) and the remaining protein requirement was met through conventional concentrate mixture of control diet (Tâ‚). All the experimental buffaloes were offered green jowar and wheat straw to meet their total DM and energy requirement. An increase (P<0.01) in milk and FCM yield was found in all the treatment groups than in Tâ‚ Rumen pH was almost unaffected due to treatments but volatile fatty acid concentration was significantly (P<0.01) higher in protected protein fed groups than in Tâ‚. Significantly (P<0.01) higher protozoal and bacterial counts were observed in treated groups than in Tâ‚ Levels of biogenic amines like tryptamine and tyramine in rumen liquor and blood in treated groups were significantly (P<0.01) lower than in Tâ‚. However, ruminal histamine concentration was significantly (P<0.05) higher in Tâ‚‚ , Tâ‚ƒ and Tâ‚„. On the contrary, circulating histamine concentration was significantly (P<0.05) lower in Tâ‚‚, Tâ‚ƒ and Tâ‚„ than in control. The concentration of total-N, ammonia-N, NPN and TCA-N in the rumen was Significantly (P<0.01) lower in Tâ‚‚ , Tâ‚ƒ and Tâ‚„ than that in Tâ‚ . The average plasma glucose and protein levels of experimental animals did not differ significantly under the various dietary treatments. However, plasma urea and anunonia nitrogen levels of animals in groups fed protected protein was significantly (P<0.01) lower than that in Tâ‚. Replacement of conventional concentrate mixture with bypass feed and addition of biopromotors are slightly beneficial in lactating buffaloes (yielding below 8 kg milk) as they increased milk production and fat percentage marginally.